Review Article :Uji Kadar Flavonoid Total Pada Simplisia Daun Kelor (Moringa Oleifera L.) Dari Berbagai Jenis Pereaksi - Shania Nurshazidah; Fajar Adi Prasetya; Lia Fikayuniar; Dinar Salma Putri Utami; Dissa Ayu Putri Andini; Gina Desfina Wijaya; Ali Alfarizzy; Muhamad Al Atoriq (Peneliti.net, 2023)
Plants have potential as therapeutic agents, for example, the moringa plant (Moringa oleifera L.) which has been used by the community to prevent and treat various types of diseases (Rudiana et al., 2020). Moringa leaves (Moringa oleifera L.) is one of the parts of the plant that can be used for its benefits as a traditional medicine (Nurcahyati, 2014). Moringa leaves (Moringa oleifera L.) are rich in β-carotene, vitamin C, vitamin E, polyphenols and flavonoids. The strategy implemented in this study was carried out by searching research journal literature for the last 10 years, namely 2013 to 2023. Scientific articles and journals were retrieved through electronic databases such as Google Scholar, PubMed, Media Neliti, Sinta Kemendikbud, Researchgate.Net and Science Direct. Literature searches and searches were carried out using related keywords such as: flavonoid levels, moringa leaf antioxidants, total flavonoid levels, moringa leaf simplicia, moringa leaves, methanol extraction, water extraction, Moringa Oleifera. Based on the results of a review article, Moringa leaves (Moringa oleifera L.) have potential flavonoids that can be used as traditional medicinal ingredients and the total flavonoid levels possessed by Moringa leaves (Moringa oleifera L.) can be influenced by the quality of simplicia, starting from temperature and storage. Flavonoid levels of Moringa leaves (Moringa oleifera L.) are also affected by the reagents and solvents used.